Evaluasi Kinerja Alat Gali Muat dan Alat Angkut Menggunakan Metode Quality Control Circle Untuk Mencapai Target Produksi Batubara Pada Tambang Terbuka PT. Allied Indo Coal Jaya, Parambahan, Sawahlunto. - Ridwan Saputra; Yoszi Mingsi Anaperta (Departemen Teknik Pertambangan FT UNP, 2021)
One of the steps to control the rate of productivity and accuracy in achieving the monthly plan is to observe or evaluate the performance of the digger fit and conveyance. This is what PT Allied Indo Coal Jaya has done in evaluating the performance of the production department in extracting coal material. Data for October 2019 shows that the planned coal production target of 30,000 tonnes / month was only achieved 16,913 tonnes / month. A production management study was conducted by applying the Quality Control Cycle (QCC) method. This method makes it possible to conduct a study of the performance evaluation of heavy equipment and the obstacles experienced during the production process. The study begins by recalculating the initial conditions by considering the mining equipment used, namely the CAT 330 Excavator and the DT Hino FM 260 JD. The actual productivity of 1 unit of Exca CAT 330 reached 21.814,173 tons / month and DT Hino FM 260 JD reached 18.767,03 tons / month with a total of 4 units of DT, the match factor of heavy equipment reached 0.65, After evaluating the Fishbone Diagram, it was found that there were major problems namely environmental factors, equipment and man power that affect working time. Performance improvement recommendations based on the Paretto Diagram, considered to optimize uptime. The results show that with increased productivity with 1 unit of exca CAT 330 equipment of 26.541,89 tons / month and 4 units of DT coal production increased by 30.289,24, the match factor of heavy equipment reached 0.85. These results indicate that the performance of the equipment can still be improved to achieve the monthly coal production target